2015
DOI: 10.1080/17451000.2015.1024130
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive cycle of the trigonal clamTivela mactroides(Bivalvia, Veneridae) in Caraguatatuba Bay, southeastern Brazil

Abstract: Tivela mactroides is an important fishery resource for local artisanal fishermen in Brazil and the establishment of management programmes for this species requires information about its reproductive cycle, the main focus of this study. The reproductive pattern of T. mactroides from Caraguatatuba Bay on the southeast coast of Brazil was analysed by means of histological techniques from November 2003 to October 2004. The species had heterogeneous continuous gametogenesis, with no resting period and the sex ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…For future mariculture of P. textile, winter and spring are the best hatchery seasons, as the current study revealed, and caution must be considered to keep temperatures within the above range. Some studies in tropical waters indicate that the studied Bivalvia species attained the highest spawning proportion during winter and spring, whereas spawning was at a minimum in summer and autumn (Denadai et al 2015). The stage V (spawning stage) peaks synchronized the timing of other stages except for the June peak at GBL, which could be due to the high female proportion during this month (the sex ratio was female-biased).…”
Section: Gonad Indexmentioning
confidence: 84%
“…For future mariculture of P. textile, winter and spring are the best hatchery seasons, as the current study revealed, and caution must be considered to keep temperatures within the above range. Some studies in tropical waters indicate that the studied Bivalvia species attained the highest spawning proportion during winter and spring, whereas spawning was at a minimum in summer and autumn (Denadai et al 2015). The stage V (spawning stage) peaks synchronized the timing of other stages except for the June peak at GBL, which could be due to the high female proportion during this month (the sex ratio was female-biased).…”
Section: Gonad Indexmentioning
confidence: 84%
“…This hypothesis was based on a mortality event in an Argentinean yellow-clam population infested by a coccid protozoan, which caused necrosis in the gills and stomach of some infested individuals (21.4%). Denadai et al [ 55 ] observed parasitism in gonads of T . mactroides in Caraguatatuba Bay in the 2003–2004 period.…”
Section: Discussionmentioning
confidence: 99%
“…Vários estudos têm sido realizados sobre Tivela mactroides no Brasil envolvendo a morfologia (Denadai et al, 2006), distribuição (Denadai et al, 2005;Medeiros et al, 2014;Rocha & Matthews-Cascon, 2015), dinâmica populacional (Denadai et al, 2015c), crescimento relativo (Turra et al, 2018), aspectos ecológicos (Turra et al, 2014), incluindo análise de predação multiespecífica (Turra et al, 2015; Batalla 2017), mortalidade (Turra et al, 2016a) e reprodução de indivíduos (Denadai et al, 2015b), bem como pesquisas voltadas para a pesca (Denadai et al, 2015a) e aspectos socioeconômicos (Turra et al, 2016b).…”
Section: Introductionunclassified